2015
DOI: 10.1073/pnas.1514680112
|View full text |Cite
|
Sign up to set email alerts
|

RNA-directed DNA methylation enforces boundaries between heterochromatin and euchromatin in the maize genome

Abstract: The maize genome is relatively large (∼2.3 Gb) and has a complex organization of interspersed genes and transposable elements, which necessitates frequent boundaries between different types of chromatin. The examination of maize genes and conserved noncoding sequences revealed that many of these are flanked by regions of elevated asymmetric CHH (where H is A, C, or T) methylation (termed mCHH islands). These mCHH islands are quite short (∼100 bp), are enriched near active genes, and often occur at the edge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
255
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(288 citation statements)
references
References 44 publications
31
255
2
Order By: Relevance
“…These observations are consistent with previous studies that demonstrated that maize TEs located near genes are targeted by 24-nt siRNA-dependent RdDM, resulting in local deposition of DNA methylation in the asymmetric CHH context in so-called CHH islands (Gent et al, 2013). Maize mutants that disrupt 24-nt siRNA accumulation show loss of CHH islands as well as instances where the flanking regions also lose CG/CHG methylation (Li et al, 2015). Our RNA-seq data show that that major effect on gene expression in the rmr6-1 mutant is a de-repression of genes that are normally lowly-or non-expressed.…”
Section: Long-term Abiotic Stresses Affect Accumulation Of Very Few Msupporting
confidence: 92%
See 2 more Smart Citations
“…These observations are consistent with previous studies that demonstrated that maize TEs located near genes are targeted by 24-nt siRNA-dependent RdDM, resulting in local deposition of DNA methylation in the asymmetric CHH context in so-called CHH islands (Gent et al, 2013). Maize mutants that disrupt 24-nt siRNA accumulation show loss of CHH islands as well as instances where the flanking regions also lose CG/CHG methylation (Li et al, 2015). Our RNA-seq data show that that major effect on gene expression in the rmr6-1 mutant is a de-repression of genes that are normally lowly-or non-expressed.…”
Section: Long-term Abiotic Stresses Affect Accumulation Of Very Few Msupporting
confidence: 92%
“…In addition, we found that the smaller numbers of genes that are down-regulated in the rmr6-1 background also show the same loss of gene-proximal siRNAs. Together, these data support the current model by which the geneflanking 24-nt siRNAs in maize primarily function to reinforce transcriptional silencing of TEs located near active genes, avoiding the spreading of euchromatin into the close TEs (Gent et al, 2013(Gent et al, , 2014Erhard et al, 2015;Li et al, 2015). The similar occupancy of RMR6-dependent, gene-flanking, 24-nt siRNA loci found for protein-coding genes and lncRNAs suggests that the CHH island system of RdDM is engaged near active genes independently of their coding or noncoding nature.…”
Section: Long-term Abiotic Stresses Affect Accumulation Of Very Few Msupporting
confidence: 79%
See 1 more Smart Citation
“…mCHH islands were first identified in maize, and have been proposed to function as 'insulators' that separate the silencing of TEs from that of nearby genes. However, there is as yet no clear conclusion about the relationship between mCHH islands and gene expression [37][38][39] . We found that mCHH islands are obvious in Ae.…”
Section: Nature Plantsmentioning
confidence: 99%
“…The CHH methylation region is more often found at the borders between heterochromatin and euchromatin that occur near genes or conserved noncoding sequences (Gent et al, 2014;Li et al, 2015c). The analyses of mutants that affect CHH methylation suggest that the function of these CHH islands is to protect/ensure the silencing of TEs from the open chromatin of nearby genes.…”
Section: Living With a New Genome Structurementioning
confidence: 99%